Soil-to-Atmosphere GHG Fluxes in Hemiboreal Deciduous Tree and Willow Coppice Based Agroforestry Systems with Mineral Soil - Andis Bārdulis; Dana Purviņa; Kristaps Makovskis; Arta Bārdule; Dagnija Lazdiņa (Land, 2023)
In this study, we estimated the magnitude of soil-to-atmosphere carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) fluxes in deciduous tree and willow coppice based agroforestry systems in hemiboreal Latvia. We studied systems combining hybrid alder, hybrid aspen, silver birch, black alder, and willow clones with perennial reed canary grass (RCG), which were established in the spring of 2011 in former cropland with mineral soil. Three different soil fertilisation practices were initially applied (control without fertilisation, fertilisation with wood ash, and sewage sludge). Measurements of fluxes of greenhouse gases were taken in both deciduous tree, willow coppice and RCG plots using a closed opaque manual chamber method, from June 2020 to October 2021. Soil CO2 fluxes (the sum of autotrophic and heterotrophic respiration) were increased in RCG plots compared to plots under willow and deciduous tree canopies, while the highest mean CH4 fluxes were found in willow coppice plots. No impact of dominant vegetation type on instantaneous soil N2O fluxes was found. Temperature was the key determinant of the magnitude of CO2 and N2O fluxes. The highest soil CO2 and N2O fluxes were detected during the summer and decreased in the following order: summer, autumn, spring, winter. There were no pronounced relationships between soil CH4 fluxes and temperature.